The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1981
DOI: 10.1017/s0043174500061993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate on the Metabolism of Phenolic Compounds: VII. Root-Fed Amino Acids and Glyphosate Toxicity in Soybean (Glycine max) Seedlings

Abstract: Several regimes of supplying exogenous aromatic amino acids to intact, 3-day-old, soybean [Glycine max(L.) Merr. ‘Hill’] seedlings by root uptake were tested to determine if growth retardation caused by root-fed, 0.5 mM glyphosate [N-(phosphonomethyl) glycine] could be reversed. Generally, root-fed levels of aromatic amino acids just below growth-retarding levels (e.g. 1 mM phenylalanine + 0.1 mM tyrosine) reversed root growth inhibition caused by glyphosate to a small (ca. 10%) but significant extent. Feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…In mature leaves, the scoparone content was higher in the glyphosate treatment at 8 DAA. Therefore, as observed by others,24 this suggests that glyphosate did not quantitatively affect phenolic compound content, but caused qualitative changes, since no significant changes were observed for total phenol contents (Table 4). Stress of many types, including that caused by herbicides, will induce synthesis of phytoalexins, so the slight increase that was observed may have been due to this type of effect 28…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In mature leaves, the scoparone content was higher in the glyphosate treatment at 8 DAA. Therefore, as observed by others,24 this suggests that glyphosate did not quantitatively affect phenolic compound content, but caused qualitative changes, since no significant changes were observed for total phenol contents (Table 4). Stress of many types, including that caused by herbicides, will induce synthesis of phytoalexins, so the slight increase that was observed may have been due to this type of effect 28…”
Section: Resultssupporting
confidence: 76%
“…It is possible that glyphosate qualitatively alters the production of phenolics without affecting the total phenolics content, for example by increasing the production of shikimate derivatives and reducing the production of aromatic amino acid derivatives 24. For this reason, the authors investigated the effect of glyphosate on the concentration of scoparone, a phenylpropanoid and one of the most important phytoalexins induced in the defence of citrus plants against plant pathogens such as Phytophthora citrophthora (Sm.…”
Section: Resultsmentioning
confidence: 99%
“…Glyphosate resulted in a 57% inhibition of protein synthesis in isolated soybean leaf cells (Tymonko 1979), but did not inhibit the uptake or incorporation of amino acids into protein by soybean [Glycine max (L.) Merr.] seedlings (Duke and Hoagland 1981). The large accumulation of free amino acids in purple nutsedge tubers Shikimic acid in glyphosate-treated tubers increased from trace levels to 0.7 mol/g fresh weight at 3 DAT (Figure 3), and the levels remained high throughout the experiment.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, uptake of amino acids, nucleotides and glucose were also found to be retarded by glyphosate in isolated cells (Brecke & Duke, 1980). Other studies (Cole et al, 1980;Duke & Hoagland, 1981) found inhibition of amino acid uptake by glyphosate not severe. Glyphosate has been reported to uncouple oxidative phosphorylation in plant (Olorunsogo et al, 1979) and mammalian (Olorunsogo & Bababunmi, 1980) mitochondria, the latter is likely to be due to altered membrane transport processes, as glyphosate was found to enhance proton permeability of mitochondrial membranes in a concentration-dependent manner (Olorunsogo, 1990).…”
Section: Other Biochemical Effects Of Glyphosatementioning
confidence: 87%